The American era-power and strategy for the 21st century : with a new postcript analyzing foreign policy after Iraq, por Robert J. Lieber, Cambridge y Nueva York : Cambridge University Press, 2007 - Wilhelmy von Wolff, Manfred (Estudios Internacionales, 2007)
-